Engagement in Online Communities by New Mothers in Recovery from Opioid Use Disorder. Issue 2 (March 2023) - Mattson, Nicole M.; Ohlendorf, Jennifer M.
Abstract: Purpose: The purpose of this study was to examine the role of engagement with online communities by women using medication-assisted treatment (MAT) to manage recovery from opioid use disorder (OUD) during pregnancy and the first year after birth. Study Design and Methods: Ten participants were identified through purposive sampling for this secondary data analysis as part of a larger grounded theory study about ways women using MAT for recovery from OUD meet the needs of their mother–infant dyad. Inclusion criteria included: English-speaking, 18 years of age or older, living in the United States, within the first year after birth, using MAT to manage OUD, and identified engaging with online communities during pregnancy and/or postpartum. A categorical-content narrative approach was used. Results: Three narratives were identified from the analysis, belonging, collaboration, and expecting success . Clinical Implications: Engagement in online communities can be a meaningful adjunct or replacement for in-person support. Online spaces are available 24/7 and allow people to join a community where they will not experience stigma and can find support tailored to their needs. Health care providers could extend their care for mothers affected by OUD by referring them to online communities for support of recovery self-management efforts. Abstract : In this qualitative study, new mothers in recovery from opioid use disorder share their experiences with participation in on-line communities. Engagement in online communities can be a meaningful adjunct or replacement for in-person support. Online spaces are available 24/7 and allow people to join a community where they will not experience stigma and can find support tailored to their needs. Nurses could extend their care for mothers affected by opioid use disorder by referring them to online communities for support of recovery self-management efforts.